Addressing Common Parental Concerns about Factors That Could Influence Piano Students’ Autonomous Motivation, Diligence, and Performance - Comeau, Gilles; Huta, Veronika (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2015)
We examined the effects of choices parents can make regarding their child’s piano lessons: age started, instruction method, taking exams, taking group lessons, sitting in on lessons, helping with home practice, giving rewards for practising. Parental choices were correlated with the following child variables regarding piano playing: autonomous motivation, interest in performance and creativity, interest in effortful practice, time spent practising, feeling of competence, and exam performance. We administered questionnaires to 173 piano students aged six to sixteen and their parents. The most beneficial predictors were: initiating lessons before age seven, sitting in on lessons, and helping with home practice.